Detection of galanin receptors in the spinal cord in experimental autoimmune encephalomyelitis - Michalickova, Danica; Kramarikova, Ivana; Ozturk, Hatice Kubra; Kucera, Tomas; Vacik, Tomas; Hrncir, Tomas; Kutinova Canova, Nikolina; Sima, Martin; Slanar, Ondrej (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2023)
AIMS: The neuropeptide galanin is a widely distributed neurotransmitter/neuromodulator that regulates a variety of physiological processes and also participates in the regulation of stress responses. The aims of the present study were to investigate the expression of galanin receptors (GalR1, GalR2, GalR3) in the spinal cords in a murine model of multiple sclerosis, experimental autoimmune encephalomyelitis (EAE) using qPCR analysis and to determine GalR1 cellular localization (oligodendrocytes, microglia, astrocytes, ependymal cells, and endothelial cells in the capillaries) by immunohistochemistry. METHODS: Twelve samples from the EAE group and 14 samples from the control group were analyzed. Spinal cords samples were obtained at the peak of the EAE disease. RESULTS: The GalR1 mRNA level was significantly decreased in the EAE mice compared with the controls (P=0.016), whereas the mRNA levels of GalR2 and GalR3 were not significantly different for the EAE and the control mice. No significant correlations were found between the severity of the EAE disease and the mRNA levels of GalR1, GalR2 and GalR3. Immunochemical detection of the GalR1 revealed its expression in the ependymal and endothelial cells. Additionally, a weak GalR1 immunoreactivity was occasionally detected in the oligodendrocytes. CONCLUSION: This study provides additional evidence of galanin involvement in EAE pathophysiology, but this has to be further investigated.
Keywords: multiple sclerosis; Animals; GalR1; galanin; Spinal Cord; Receptor, Galanin, Type 2; immunohistochemistry; GalR2; Receptors, Galanin; Mice; mícha; messenger RNA; Endothelial Cells; myši; encefalomyelitida autoimunitní experimentální; RNA, Messenger; experimental autoimmune encephalomyelitis; receptory galaninové; GalR3; endoteliální buňky; Galanin; receptor galaninu typ 2; Encephalomyelitis, Autoimmune, Experimental; mRNA; zvířata